1997
DOI: 10.1143/jjap.36.2998
|View full text |Cite
|
Sign up to set email alerts
|

Single Process to Deposit Lead Zirconate Titanate (PZT) Thin Film by a Hydrothermal Method

Abstract: The hydrothermal method to deposit lead zirconate titanate (PZT) thin film is a new method reported by Tsurumi et al.. in 1991. This method consists of two linked processes. We have found that the film deposited by the first process is not PZT but separated lead zirconate (PZ) and lead titanate (PT). In this paper, we report that a PZT thin film was successfully deposited by a single process. The chemical construction and composition of the film were analyzed. The Zr/(Zr+Ti) ratio of the PZT film wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 5 publications
0
46
0
2
Order By: Relevance
“…For example, Ohba et al, 1994, observed a steep gradient of chemical composition between a substrate and a PZT layer: an interfacial Ti-rich PZT layer with low piezoelectric constant near the substrate. Contrary to this result, Morita et al, 1997, reported that separated PTO and PZO layers were deposited during the nucleation process; the PTO layer grew during the first 2 h of the nucleation process, followed by the PZO film growth (Fig. 7, Case 3).…”
Section: Gradient In Pzt Thin Films Prepared By Sputtering and Hydrotmentioning
confidence: 62%
“…For example, Ohba et al, 1994, observed a steep gradient of chemical composition between a substrate and a PZT layer: an interfacial Ti-rich PZT layer with low piezoelectric constant near the substrate. Contrary to this result, Morita et al, 1997, reported that separated PTO and PZO layers were deposited during the nucleation process; the PTO layer grew during the first 2 h of the nucleation process, followed by the PZO film growth (Fig. 7, Case 3).…”
Section: Gradient In Pzt Thin Films Prepared By Sputtering and Hydrotmentioning
confidence: 62%
“…Пленки сложных оксидов получают методами хими-ческого осаждения металлорганических соединений из газовой фазы (metalorganic chemical vapour depositions, MOCVD) [26,27], импульсного лазерного осаждения (pulsed laser deposition, PLD) [28], высокочастотного магнетронного распыления [29][30][31], гидротермальным методом [32], методами химического осаждения из рас-творов (chemical solution deposition, CSD), включая золь-гель метод [33,34], а также методами молекулярно-лучевой эпитаксии (MBE) [35].…”
Section: Introductionunclassified
“…Examples include the hydrothermal method (5) , the sol gel process (6) , the MOCVD method (7) and the sputtering method (8) - (10) . Table 1 indicates X-ray diffraction (XRD) data and thin film PZT produced by various deposition techniques (11) - (13) , and piezoelectric properties (d 31 ) for bulk Table 1 Piezoelectric constant and XRD intensity for PZT deposited by various thin film process* (11), ** (12), ***PZT produced by the Fuji ceramics company (14) .…”
Section: Introductionmentioning
confidence: 99%